INTERKONEKSI DAN PEMBANGUNAN E-GOVT - Ari Cahyo Nugroho (Jurnal Studi Komunikasi dan Media, 2015)
The background of this study is interconnection phenomenon that has hardly examined. This one focuses on questioning the network interconnection structure application in the public service, including e-govt. The results show that Interconnection network structure has been already adopted. The ability of computer radius  between computers is 5-10 km, with 10-100 Mbps bandwitch, with LAN Network Interconnection Structure. Router and gateway are already interconnected, except LAN. In overall, LAN is the network structure with related phenomenon, the stage of e-gov adopted in goverment, variants of 12 question was done in the development of e-govt agencies context. There are 3 that adopted: information site creation, human resources preparation, and internal dissemination of information sites. The level of e-govt development phase are divided into 4: preparation, maturation, consolidation and utilization. But generally, the level is in the preparation phase. The public has not be able to enjoy public service. The condition is not favorable to the public caused by a number factors of humanity (such as culture of sharing-sharring the information; culture of documentation). This increased interconnection implementation related and e-govt ahead requires an urgence of implementation of socializing and technical guidance related to implementation of interconnection and e-govt in the Government apparatus.Key words: Interconnection; Development; E-Govt.  ABSTRAKBerlatarbelakangkan fenomena interkoneksi yang hampir belum pernah diteliti,  penelitian fokus mempertanyakan penerapan struktur jaringan interkoneksi di instansi pelayanan publik bidang informasi dan dokumentasi dan termasuk kualitas tahapan pembangunan e-govt di instansi bersangkutan. Hasilnya menunjukkan struktur jaringan interkoneksi umumnya sudah diadopsi namun masih cukup banyak juga belum mengadopsi. Kemampuan jarak tempuh antar komputer yang sudah terkoneksi berkisar 5-10 km. Bandwhitch-nya 10-100 Mbps. Lingkup struktur jaringan interkoneksi itu bersifat LAN. Router dan gateway sudah dimiliki namun LAN-LAN itu belum terinterkoneksi. Secara overall struktur jaringan interkoneksi yang diadopsi itu, yaitu jaringan interkoneksi LAN. Terkait fenomena Tahapan e-government yang diadopsi di instansi, maka 12 varian persoalan sudah dilakukan dalam konteks pembangunan dan pengembangan e-govt instansi. Namun tiga yang banyak diadopsi : pembuatan situs informasi, penyiapan sdm, dan sosialisasi situs informasi untuk internal. Level tahapan pengembangan e-govt terbagi empat: persiapan, pematangan, pemantapan dan pemanfaatan. Namun umumnya level itu baru dalam tahap persiapan. Karenanya publik jadi relatif belum dapat menikmati layanan publik. Kondisi tidak menguntungkan publik tersebut disebabkan sejumlah faktor humanity (seperti kultur berbagi-sharring informasi); kultur dokumentasi). Terkait ini peningkatan implementasi interkoneksi dan e-govt ke depan memerlukan urgensi pelaksanaan sosialisasi dan bimbingan teknis terkait implementasi interkoneksi dan e-govt  di kalangan aparatur pemerintah.Kata-kata kunci : Interkoneksi ; Pembangunan; E-Govt.